Effect of TiO2 nanofibres on selected bronchoalveolar parameters in acute and subacute phase--experimental study - Hurbánková, Marta; Černá, Silvia; Dzirbíková, Zuzana; Wimmerová, Soňa; Hrašková, Dominika; Marcišiaková, Jana; Moricová, Štefánia (Central European Journal of Public Health, 2013)
Titanium dioxide nanofibres (TiO2) were intratracheally instilled in dose of 4 mg/0.2 mL saline solution per animal (Wistar rats). After 48 hours and 14 days the animals were exsanguinated (under i.p. thiopental narcosis), bronchoalveolar lavage (BAL) was perfomed and cells from BAL fluid were isolated. Following inflammatory, cytotoxic and oxidative stress BAL parameters were examined: differential cell count (% of alveolar macrophages (AM), polymorphonuclears and lymphocytes); the viability and phagocytic activity of AM; the proportion of immature cells; the proportion of multinucleated cells; count of AM/mL lavage; count of BAL cells/mL lavage; the level of ascorbic acid and activity of superoxide dismutase, both in tissue homogenate and in bronchoalveolar lavage fluid. The majority of examined BAL parameters in the acute and subacute phase in our study suggest serious inflammatory and cytotoxic processes in lung after exposure to TiO2.
Keywords: Titanium; Oxidative Stress; titan; zvířata; alveolární makrofágy; Animals; Leukocytes; Inflammation Mediators; potkani Wistar; Bronchoalveolar Lavage Fluid; Rats; nanovlákna; mediátory zánětu; oxidační stres; Nanofibers; bronchoalveolární lavážní tekutina; krysa rodu Rattus; Rats, Wistar; leukocyty; Macrophages, Alveolar